ANALISIS KELAYAKAN APLIKASI TIKTOK SEBAGAI MEDIA PROMOSI HOME INDUSTRI TINJAUAN ASPEK PEMASARAN - Ni Made Peni Priantari; Anak Agung Elik Astari; Ni Luh Indiani (Nusantara Hasana Berdikari, 2022)
In the midst of competition for similar businesses that are very tight, being able to fulfill market desires is an expectation for all business actors. The use of the TikTok application as a home industry promotional medium has been very commonly used in the recovery of this pandemic. Based on the results of the research and analysis that the researchers have described, it can be concluded that the sales method carried out with tiktok media has a considerable influence on the increase in revenue at The Nu Mesari Home Industry, compared to the previous year's revenue which only used whatsapp media and direct visits. The proposed promotion through tiktok media at The Nu Mesari Home Industry is feasible to run because it has a positive NPV value, the IRR value is 13.7%, the PI value is greater than 1, namely 1.3%, so it is said that fruit Salad UD NU Mesari innovation is worth investing in and running business operations with a fairly fast return on investment from this business, which is 2 years 5 months 2 days.